EXPLORING STUDENTS’ MOTIVATION IN WRITING RESEARCH PAPER AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Mori Manjusri (PBI 15 UMY 056, 2015)
*56 Motivation is one of the most important things for students. There are many motivations for students in learning, especially in writing research paper. At English Education Department of Universitas Muhammadiyah Yogyakarta for instance, several students are motivated to write research paper. It is based on the number of students who write and present papers in the conferences. Hence, the purpose of this research is to find out types of students’ motivation and students’ obstacles in writing research paper at English Education Department of Universitas Muhammadiyah Yogyakarta. The method used in this research is qualitative. The respondents consisted of three students at English Education Department of Universitas Muhammadiyah Yogyakarta. They had written and presented their paper in the conference. To get the data, the researcher interviewed them. After that, the researcher transcribed the data from the respondents and analyzed it with coding. The findings of research showed that types of students’ motivation in writing research paper at English Education Department of Universitas Muhammadiyah Yogyakarta was classified as intrinsic and extrinsic motivation. The students’ intrinsic motivations in writing research paper were getting self- pride, improving writing skill, adding new knowledge and experience, and applying knowledge. Meanwhile, students’ extrinsic motivations in writing research paper were joining conference, acquiring scholarship, showing personal capability, and influenced by university teaching and learning environment, such as from their lecturers, subject course, and close friend. On the other hand, students’ obstacles in writing research paper were lack of understanding in researching, having issues with writing, procrastination, time management, lack of facilities and uncooperative partners of research.